An explorative digital tool as a pathway to meaning: the case of the inflection point. (25th March 2022) - Kouropatov, Anatoli; Ovodenko, Regina
Abstract: The learning of calculus concepts is considered challenging for students. This claim is actual for calculus in general and for specific concepts in particular. In this paper, we focus on the concept of the inflection point. We argue that one of the roots of this problem is the lack of a useful and productive meaning of the concept—the understanding of the inflection point as the point where the behaviour of a curve (graph of function) changes in relation to the tangent line. With the purpose of helping students to construct this meaning we developed a specific digital tool: a teaching unit based on the interactive diagrams framework. Does this tool help students to achieve this meaning (i.e., to construct and consolidate new knowledge)? To answer this question, we conducted an empirical feasibility experiment (in the form of a case study with two first-year students from the Industrial Engineering College) and analysed the gathered data using the framework of abstraction in context as the theoretical and methodological basis. Our findings show that the designed tool (the interactive digital teaching unit) has potential for helping students to make the above-mentioned meaning for this mathematical concept and can serve as a useful basis to continue the investigation of designing tools that support the meaning-making of advanced mathematical concepts.